Sustainability, Livelihoods, and Quality of Life of Older Retirees in Lagos State, Nigeria - Bola Amaike (Journal of Global Initiatives, 2016)
Later life is celebrated in Africa because it is seen as a blessing from God. Therefore, older people are generally treated with dignity. But with modernization, African senior citizens suffer diverse challenges and experience difficulty in meeting their basic needs. Hence, the need for sustainable livelihoods that will address life deprivations and improve the quality of life of Nigerian elders. This article examines the sustainability of retirement livelihoods and its impact on quality of life of formal sector retirees in Nigeria. It argues that beyond the conventional survival mechanisms, Nigerian retirees require resilient and sustainable livelihoods in order to enhance their quality of life. Life course perspective and activity theory are adopted as explanatory tools. With the aid of a multi-stage systematic sampling method, 1,321 Nigerian retirees in Lagos State were studied to examine their livelihoods and quality of life. Empirical data reveal that access to multiple sources of income promotes sustainability of retirement livelihoods and quality of life with private sector retirees being more empowered and adequately protected against life vicissitudes. This culminates in vulnerability and precarious living conditions of public sector retirees. The article concludes with the need to strengthen formal and informal social supports in order to improve retirement livelihoods and promote quality of life of retirees.